The Effect Of The Numbered Heads Together (Nht) Project-Based Cooperative Learning Model On The Interests And Mathematics Learning Outcomes Of Grade Iv Students - Syalsa Nabila Nurdin; Wahyullah Alannasir; Jusmaniar Jusmaniar (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
Mathematics learning in elementary schools often faces challenges in the form of low student interest and learning outcomes. This occurs because the learning process still tends to be one-way, so that students are less actively involved and less motivated in understanding concepts. This condition requires teachers to implement more innovative, interactive, and student-centered learning models to increase their involvement and understanding. Based on these problems, this study was conducted to determine the effect of the project-based Numbered Heads Together (NHT) cooperative learning model on the interest and learning outcomes of fourth-grade students at MI An-Nashar Timor-Timur, Makassar City. The study used an experimental method with a One Group Pretest-Posttest design involving 20 students as a sample. Research data were obtained through learning outcome tests, learning interest scores, and teacher and student observation sheets. All data were analyzed using normality tests, homogeneity tests, and hypothesis testing through ANOVA. The results showed that the application of the project-based NHT model was able to increase student interest in learning from the low category to the high category, as well as improve learning outcomes from the very low category during the pretest to the high category in the posttest. Teacher and student activity also experienced a significant increase. Statistical tests showed a significance value <0.05, indicating that the project-based NHT model had a positive and significant impact on mathematics interest and learning outcomes. Therefore, this study concluded that the project-based Numbered Heads Together (NHT) model is effective in improving the quality of mathematics learning in elementary schools.